2009
DOI: 10.1124/dmd.109.031138
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of Psilocin and 4-Hydroxyindole by the Human UDP-Glucuronosyltransferases

Abstract: ABSTRACT:We have examined the glucuronidation of psilocin, a hallucinogenic indole alkaloid, by the 19 recombinant human UDP-glucuronosyltransferases (UGTs) of subfamilies 1A, 2A, and 2B. The glucuronidation of 4-hydroxyindole, a related indole that lacks the N,N-dimethylaminoethyl side chain, was studied as well. UGT1A10 exhibited the highest psilocin glucuronidation activity, whereas the activities of UGTs 1A9, 1A8, 1A7, and 1A6 were significantly lower. On the other hand, UGT1A6 was by far the most active e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…After absorption within circulatory system the conversion of psilocin to glucuronide is mediated by UGT1A9. 126 Other identified psilocin metabolites, namely 4-hydroxy-3-yl-acetic acid 4HIAA, 4-hydroxy-3-yl-acetaldehyde 4HIA, and 4-hydroxytryptophol 4I-IT, are the products of its deamination and oxidation. 114,122 …”
Section: Methods Of Qualitative Analysis and Isolationmentioning
confidence: 99%
“…After absorption within circulatory system the conversion of psilocin to glucuronide is mediated by UGT1A9. 126 Other identified psilocin metabolites, namely 4-hydroxy-3-yl-acetic acid 4HIAA, 4-hydroxy-3-yl-acetaldehyde 4HIA, and 4-hydroxytryptophol 4I-IT, are the products of its deamination and oxidation. 114,122 …”
Section: Methods Of Qualitative Analysis and Isolationmentioning
confidence: 99%
“…Total RNA was isolated with RNA-Bee system (Tel-Test Inc., Friendswood, TX), according to the manufacturer's manual and as described previously . Levels of UGT1A1, UGT1A9, and UGT2B7 mRNAs were determined by real-time polymerase chain reaction (PCR) (model 7300; Applied Biosystems, Foster City, CA) with SYBR Green detection as previously described with minor modifications (Manevski et al, 2010). Quantitative PCRs (25 l) included SYBR Green 2ϫ Master Mix (Applied Biosystems), 10 l of diluted cDNA, and 100 nM of each primer (200 nM for 18S RNA).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, more than 80% of the psilocin administered to humans is metabolized to psilocin glucuronides. In vitro psilocin glucuronidation also has been studied using 19 recombinant human UDP glucuronosyltransferases of the subfamilies 1A, 2A and 2B [10]. Holzmann et al [1] have shown that psilocin may undergo enzymatic oxidation in humans to form 4-hydroxytryptophole (4-HT) and 4-hydroxyindole-3-acetaldehyde, which may be further metabolized to 4-HIAA.…”
Section: Introductionmentioning
confidence: 99%